CULTURAL ENCODING THROUGH GAME MECHANICS: STRATEGY AND SYMBOLISM IN INDIAN BOARD GAMES - Vaidya, Yogindra; Kaushik, Hemant (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This research examines how game mechanics in traditional Indian board games encode cultural values, strategies, and symbolism, fostering identity and social learning among young adults aged 18-22. Drawing from classics like Pachisi, Snakes and Ladders (Moksha Patamu), and Chaupar, the study explores mechanics such as dice-driven movement (representing karma and chance), ladder ascents (symbolizing dharma and opportunity), and snake descents (embodying moral pitfalls). These elements strategically balance luck and skill, embedding Hindu-Buddhist philosophies of reincarnation, ethical decision-making, and communal harmony. A mixed-methods approach combines qualitative case studies with targeted data collection across four sites: Gurgaon (urban design hubs), Kashipur and Uttarakhand (rural cultural preserves), and MIT College, Pune (academic game design programs). Primary data includes 120 semi-structured interviews and playtesting sessions with 18–22-year-old students (n=80 per site), surveys on mechanic interpretations (n=200), and ethnographic observations of gameplay adaptations. Secondary sources encompass historical texts and modern redesigns. Findings reveal that 78% of participants recognized symbolic mechanics as direct cultural metaphors, enhancing engagement and retention of values like patience and strategy. Urban youth (Gurgaon, Delhi-NCR) favoured hybridized mechanics for digital ports, while rural groups (Kashipur, Uttarakhand) emphasized communal rituals, with 65% linking snakes/ladders to personal ethics. Mechanics proved effective for ages 18-22, boosting critical thinking by 42% in post-play assessments, though modernization risks diluting symbolism.